Evaluating the geomechanical properties of Cambay Shale, Cambay Basin, India using advanced wireline logs for shale hydrocarbon exploration. (18th June 2021) - De, Sanjukta; Sengupta, Debashish
Abstract: Brittleness index (BI) is an important parameter in evaluation of rock frackability. Two different methods are used to estimate continuous BI of Cambay Shale of Jambusar-Broach block, Cambay Basin, India, using advanced logs like ECS, Sonic Scanner (SS) and mineralogical analysis of core samples by XRD. First method is based on mineral composition using ECS log and second method is based on elastic moduli using SS log. ECS-based BI is in good agreement with BI from XRD-based mineralogy. BI estimated by two log-based methods will provide a cost effective and continuous information to identify potential regions for effective hydro-fracture.